The Broadband Nonlinear Optical Response in Graphene/MoS2/Ag Thin Films at Near Infrared - Sun, Di; Fang, Yu; Yan, Xiaoyan; Shan, Wen; Sun, Wenjun; Meng, Qingyu (Frontiers in Materials, 2021)
Graphene/MoS2/Ag thin films were successfully prepared by the magnetron sputtering technique and liquid phase exfoliation. Structure, morphology, optical properties, and nonlinear optical characteristics of the graphene/MoS2/Ag and graphene/MoS2 thin films were studied by X-ray diffractometer, spectrophotometer, field-scanning electron microscope, and femtosecond (fs) Z-scan technique. The results of the fs Z-scan experiment indicate that the graphene/MoS2/Ag thin films exhibit reverse saturable absorption properties due to the free carrier absorption and two-photon absorption. More importantly, with the increase of DC magnetron sputtering power (from 5 to 15 W), the local surface plasmon resonance effect of the Ag thin films increases, which leads to the enhancement of nonlinear optical properties of the graphene/MoS2/Ag thin films. The nonlinear absorption coefficients of the graphene/MoS2/Ag thin films are increased from 1.14 × 10–10 to 1.8 × 10–10 m/W at 800 nm and from 4.79 × 10–11 to 6.79 × 10–11 m/W at 1,030 nm, and the nonlinear refraction index of the graphene/MoS2/Ag thin films is -4.37 × 10–17∼−4.18 × 10–16 m2/W under the excitation of 800 and 1,030 nm, respectively. Moreover, when the graphene/MoS2/Ag thin films were excited at 800 and 1,030 nm, respectively, the nonlinear figure of merit values of the graphene/MoS2/Ag thin films are increased from 1.23 to 2.91 and from 1.30 to 1.47, which are enough to support the application of the graphene/MoS2/Ag thin films in the field of all-optical switching applications.